Marginalization and Political Agitations in Multi-ethnic Nation - Eleje, Joy Ngozi (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
Marginalization, conceptually and empirically is a phenomenon not new in the Nigeria socio-political lexicon; as it has remained a recurring decimal attracting local, national and global debates. In the case of Nigeria, marginalization is multi-dimensional but its politicization constitutes a negative omen confronting the peace, stability and development of the Nigerian federal arrangement. As presently constituted Nigeria is faced with worrisome hues and cries of ethno-religious marginalization, youth and women marginalization, economic and political marginalization evident across states, tribes, ethnicities, religions and gender. The agglomeration and persistence of all these bring to question the sincerity of the political leadership and the essence of Nigeria federal system of government. It is consequent on the above concerns and the apparent lack of trust on the system that the country is today riddled with incessant political agitations that are fast consuming the heart of the Nigerian state. This paper, therefore, is a modest contribution in the quest for true Nigerian federalism that upholds inclusivity across the board as sacrosanct for a more united and progressive Nigeria for all in the spirit of justice, equity and fairness. The paper explored marginalization and political agitations in Nigeria as a multi-ethnic nation with focus on issues, challenges and prospects for a politically inclusive modern Nigeria.